2015
DOI: 10.1177/0960327115600370
|View full text |Cite
|
Sign up to set email alerts
|

Hazards identified and the need for health risk assessment in the South African mining industry

Abstract: Although mining plays a prominent role in the economy of South Africa, it is associated with many chemical hazards. Exposure to dust from mining can lead to many pathological effects depending on mineralogical composition, size, shape and levels and duration of exposure. Mining and processing of minerals also result in occupational exposure to toxic substances such as platinum, chromium, vanadium, manganese, mercury, cyanide and diesel particulate. South Africa has set occupational exposure limits (OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 69 publications
1
20
0
1
Order By: Relevance
“…SA's main raw materials mined are gold, diamonds, platinum, chromium, vanadium, manganese, uranium, iron, coal and copper. Scientific studies have confirmed that mining of any of these minerals presents health hazards; hence human exposure to them should be monitored as well as the environment in which their use occurs 30 . However, the spectrum of tests requested for biological and environmental monitoring at the Analytical Services is not representative of this variety of raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…SA's main raw materials mined are gold, diamonds, platinum, chromium, vanadium, manganese, uranium, iron, coal and copper. Scientific studies have confirmed that mining of any of these minerals presents health hazards; hence human exposure to them should be monitored as well as the environment in which their use occurs 30 . However, the spectrum of tests requested for biological and environmental monitoring at the Analytical Services is not representative of this variety of raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…respiratory ailments) experienced by people who live in or near such areas (Edmeston, 2010;Radio Netherlands Worldwide, 2012;Utembe, Faustman, Matatiele, & Gulumian, 2015). Recent literature speculates on the possible effects of polluted water and mine drainage in the broader UpperWonderfonteinspruit environment near which especially the Bekkersdal informal settlement is situated (Coetzee, Winde, & Wade, 2006;Environment News South Africa, 2010;Liefferink, 2015;Winde, 2009).…”
Section: Bekkersdalmentioning
confidence: 99%
“…The adjacent Donaldson Dam in the Upper-Wonderfonteinspruit, for example, is known for the unacceptably high levels of radioactivity in its sediment (Liefferink, 2015;Winde, 2009). Utembe et al (2015) indicate that mining in South Africa is associated with various chemical and health hazards. Amongst others, the dust that is produced as a result of mining, can result in a variety of pathological effects and mining and processing of minerals can result in exposure to toxic substances such as platinum, chromium, vanadium, and so forth (Utembe et al, 2015).…”
Section: Bekkersdalmentioning
confidence: 99%
See 2 more Smart Citations